2016
DOI: 10.1007/s00125-016-3919-2
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAcase deficiency suppresses skeletal myogenesis and insulin sensitivity in mice through the modulation of mitochondrial homeostasis

Abstract: Aims/hypothesis O-GlcNAcylation is implicated in modulating mitochondrial function, which is closely involved in regulating muscle metabolism. The presence of O-GlcNAcase (OGA), the enzyme involved in the removal of O-GlcNAc, in mitochondria was recently confirmed in rats. In the present study, we investigated the regulation of myogenesis and muscle insulin sensitivity to OGA in mice, with a focus on mitochondria. Methods C57BL/6J mice fed a high-fat diet for 4 months were used to observe mitochondrial density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 45 publications
1
35
0
Order By: Relevance
“…Myogenic differentiation is associated with mitochondrial biogenesis and an increased reliance on oxidative phosphorylation 34 , 39 . Furthermore, alterations in myogenic differentiation capacity and mitochondrial function often coexist 40 42 . Therefore, a Seahorse® XF Mito Stress Test was conducted on myotubes that had been differentiated for 8 d with or without the presence of 5 ng/mL recombinant resistin (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Myogenic differentiation is associated with mitochondrial biogenesis and an increased reliance on oxidative phosphorylation 34 , 39 . Furthermore, alterations in myogenic differentiation capacity and mitochondrial function often coexist 40 42 . Therefore, a Seahorse® XF Mito Stress Test was conducted on myotubes that had been differentiated for 8 d with or without the presence of 5 ng/mL recombinant resistin (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, an increase in lipid content in type I fibres appears to be a feature of sedentary, but not physically active ageing 63 . The effect of IMCL accumulation on skeletal myogenesis is less well established, but O-GlcNAcylation, a post-translational modification that is associated with obesity and diabetes, has a detrimental effect on C2C12 myogenesis 40 . Given these findings, the functional effects of resistin on muscle metabolism we report here may have important implications.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies using comparative O-GlcNAc profiling of mitochondria from control and diabetic rat hearts identified many proteins that had site-specific alterations in O-GlcNAcylation in response to diabetes [60]. These recent insights into O-GlcNAcylation of mitochondrial proteins have provided a better understanding of the mechanisms by which elevated O-GlcNAc levels contribute to the adverse effects of diabetes, but will also usher in new insights into the cardioprotective mechanisms associated with acute increases in O-GlcNAcylation [61]. …”
Section: Diabetes and The Heartmentioning
confidence: 99%
“…On the other hand, as we begin to understand more about the cellular functions regulated by protein O-GlcNAcylation it is increasingly clear that a more accurate concept would be that O-GlcNAc modification of cardiovascular proteins is a dynamic process that is critical in maintaining normal cardiomyocyte function. This is reinforced by the observations that O-GlcNAcylation of proteins plays a role in regulating fundamental cellular processes ranging from transcription to metabolism; there is also emerging evidence to suggest that protein O-GlcNAcylation also contributes to regulation of autophagy, epigenetics, and mitochondrial biogenesis [4, 51, 61]. Consequently, the context in which O-GlcNAc levels are changed are as specific as the stimuli, cell type or disease state with regard to its effect on cell function.…”
Section: Future Implicationsmentioning
confidence: 99%
“…These observations indicate a potential role for O-GlcNAcylation in glucose metabolism in mammals. Indeed, previous studies in cultured cells have demonstrated that O-GlcNAcylation is involved in glucose metabolism in the liver [11], skeletal muscle [12] and adipose tissues [13], and accelerates insulin secretion in pancreatic beta cells [14]. However, little is known about the physiological roles of this posttranslational modification in glucose metabolism in vivo because congenital Ogt-knockout (KO) mice are embryonic lethal [15].…”
Section: Introductionmentioning
confidence: 99%